TERRITORIAL CHARACTERISTICS OF SECONDARY METAL WASTE MARKET (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides feedback on improving the efficiency of collection and processing of secondary ferrous scrap. Recommendations for the collection of secondary ferrous metal fragments are given.